Tauhid dan Takdir - Zainun Kamaluddin Fakih (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2003)
This paper explores the topics of tawhid and destiny, examining the relationship between Allah and humanity. In this discussion, several important questions arise, such as: To what extent does the power of Allah the Almighty relate to human actions? Do humans have freedom in their actions, or is everything predetermined by Allah’s will, making humans like puppets that do not move without the puppet master’s direction? Has Allah predetermined the course of human life from the beginning? And is the fate of humans, both good and bad, already decided by Allah, with humans merely living out their destiny? Other relevant questions include whether the determination of entry into paradise or hell is an divine decree. Through analyzing these questions, this paper aims to explore the dynamics between Allah’s power and human freedom, as well as its implications for our understanding of destiny and moral responsibility.